Sugar Metabolism in Stone Fruit: Source-Sink Relationships and Environmental and Agronomical Effects - Falchi, Rachele; Bonghi, Claudio; Drincovich, María F.; Famiani, Franco; Lara, María V.; Walker, Robert P.; Vizzotto, Giannina (Frontiers in Plant Science, 2020)
The partitioning of assimilates in fruits, which are economically important sink organs, is ruled by different physiological processes and affected by both environmental and agronomical factors. The bulk of the water and solutes, required for the growth, is imported into fruits and seeds through xylem and phloem. In the stone fruits, five vascular bundles enter the base of the fruit, then dividing to supply either the flesh or the seed. The main sugars accumulated in stone fruits include fructose, glucose, and sucrose, along with other minor saccharides. The mechanisms of phloem loading in these fruit species have not been fully elucidated yet, but the available data hint either an apoplastic or a symplastic type, or possibly a combination of both, depending on the species and the sugar considered. Similarly, phloem unloading mechanisms, elucidated for a small number of species, depend on genotype and developmental stage. Remarkably, key enzymes and transporters involved in the main sugars-conversion and transport pathways have received considerable attention. In stone fruit trees, the presence of an elevated number of fruits alters the source-sink balance, with a consequent intensification of competition among them and between vegetative and reproductive growth. The main environmental factors affecting this balance and the agronomical/artificial manipulations of source-sink relationships to achieve adequate fruit production and quality are reviewed.